2006
DOI: 10.1186/1471-2334-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream and endovascular infections due to Abiotrophia defectiva and Granulicatellaspecies

Abstract: Background: Abiotrophia and Granulicatella species, previously referred to as nutritionally variant streptococci (NVS), are significant causative agents of endocarditis and bacteraemia. In this study, we reviewed the clinical manifestations of infections due to A. defectiva and Granulicatella species that occurred at our institution between 1998 and 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 41 publications
2
61
1
3
Order By: Relevance
“…Bouvet reported that cases of endocarditis caused by these bacteria exhibit much higher rates of treatment failure, relapse, and death than those attributable to other viridans group streptococci [14]. This pathogen has the ability to bind to the host extracellular matrix, which may play a major role in its ability to cause endocarditis and other endovascular infections, especially in neutropenic patients [17]. Granulicatella also has the ability to bind to fibronectin, facilitating intravascular infections, including endocarditis [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouvet reported that cases of endocarditis caused by these bacteria exhibit much higher rates of treatment failure, relapse, and death than those attributable to other viridans group streptococci [14]. This pathogen has the ability to bind to the host extracellular matrix, which may play a major role in its ability to cause endocarditis and other endovascular infections, especially in neutropenic patients [17]. Granulicatella also has the ability to bind to fibronectin, facilitating intravascular infections, including endocarditis [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the virulent potential of this organism is well established, and it has been implicated in numerous diseases far more harrowing than halitosis. Many reported infections involved immunocompromised patients, and the most common infections were sepsis and endocarditis, with more than 20 such cases reported [14][15][16][17]. The organism also has been associated with meningitis, osteomyelitis, peritonitis, various abscesses, pneumonia, and severe infections of foreign bodies such as pacemaker wires or prosthetic valves [18][19][20][21][22][23][24][25][26][27].…”
mentioning
confidence: 99%
“…Prior dental manipulations in past six months have emerged as a contributory factor for IE in the majority of reports. Most commonly affected valves are aortic valves and mitral valves.. 3,[8][9][10][11][12] In most cases the disease course is slow and indolent. Embolizations occur in one third of patients in the absence of classical symptoms of digital clubbing, Osler's nodes and petechiae.…”
Section: Discussionmentioning
confidence: 99%
“…cause infections such as endocarditis, bacteremia, keratoconjunctivitis, CNS infections, otitis, osteomyelitis, and pancreatic abscess. 8 Rates of oral colonization by Granulicatella exceed that of Abiotrophia, prompting to assign oral cavity as the major source of infections. 9 Fastidious nature of growth and high prevalence of beta-lactam and macrolide resistance may pose challenge to treat invasive infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation